BLOCKCHAIN TECHNOLOGY AND SMART CONTRACTS: LEGAL IMPLICATIONS AND FUTURE REGULATIONS - Edison Hatoguan Manurung (Law Studies and Justice Journal (LAJU), 2025)
In recent decades, digital technologies, especially blockchain and smart contracts, have significantly changed the legal and contractual paradigm. However, the main challenge faced is the legal uncertainty regarding the recognition and enforcement of smart contracts in various jurisdictions. This research aims to explore how smart contracts can be recognized and enforced within existing legal frameworks in various legal systems, including common law and civil law. Using a Systematic Literature Review (SLR) approach, this research identifies, analyzes and synthesizes relevant literature from leading academic databases. Strict inclusion and exclusion criteria were applied to ensure the validity and relevance of the data. The findings show that legal recognition of smart contracts varies significantly between countries, with some countries having adopted supportive regulations, while others are still stuck in traditional legal interpretations. This research also identifies the urgent need for harmonization of international law to address existing uncertainties. These findings have important implications for policy makers and legal practitioners, highlighting the need for legal reform that is responsive to technological innovation. This research contributes to the development of more adaptive legal theory and practice in facing digital challenges.